Problems in higher education in the state of Veracruz when applying linear programming (Nexo Revista Científica, 2020)
In operational research, the linear programming technique applies various methods to solve mathematical programming models, it relies on matrix algebra to arrive at the solution of the problem, however, a problem that arises during the optimization process is the need to work with rational numbers, which causes that the ignorance to carry out the operations and the inadequate handling of the calculating machines causes that the solution of the problem in question is wrong. This problem impacts on the learning of the operations or related research subject, taught in the educational programs of the Technological Institutes of the State of Veracruz.